The effect of educational intervention based on the PEN-3 model on breast cancer screening behaviors - Shoushtari-Moghaddam, Elaheh; Shahnazi, Hossein; Hassanzadeh, Akbar (Frontiers in Public Health, 2023)
Background: Breast cancer is the most important malignancy and the main cause of cancer deaths among women worldwide. Breast cancer screening is an effective way to reduce breast cancer deaths.The present study aimed to provide breast cancer screening behavior training for female teachers in Isfahan, Iran.Material and methods: This randomized controlled trial included 120 teachers who have randomly divided into two groups (60 in the control group and 60 in the intervention group).The data collection tool was a PEN-3 model-based questionnaire. Four 90-minute training sessions were held for the intervention group to modify perception and enablers. Breast selfexamination (BSE), Clinical breast exam (CBE), and mammography (MMG) were investigated in both groups before and after six months after the last training using SPSS20 and appropriate statistical tests.The frequency of BSE (P= 0.02), CBE (P= 0.04), and MMG (P= 0.01) in the intervention group was significantly higher than in the control group six months after training.The mean scores of perception and enablers were significantly higher in the intervention group than in the control group 3 and 6 months after training (p<0.001). The logistic regression analysis indicated that perception factors were the strongest predictors of breast cancer screening behavior in teachers.Results of the present study indicated that using the PEN-3 model in the educational intervention was effective in improving breast cancer screening behavior.